我國中小學教師專業標準之研究 The Professional Standards of Elementary and Secondary School Teachers in Taiwan - 林政逸 Jeng-Yi Lin; 賴慧君 Hui-jun Lai (National Changhua University of Education, 2021)
自 1990 年以降，標準本位 (standard-based) 師資培育為世界師資培育發展趨勢。我國教育部 2016 年公布《中華民國教師專業標準指引》，落實標準本位師資培育，教師專業標準成為發揮引領師資職前教育以及在職教師專業發展的功能。本研究除透過文獻以探究美國、英國及我國教師專業標準內容之外，另外，實施 2 回合德懷術問卷，以了解專家學者、主管教育行政機關主管及中小學校長等 12 位專家學者，對我國教師專業標準適切性、落實情形，以及未來改善方向之看法。本研究結論如下： 一、我國 10 項教師專業標準，呈高度適切性。 二、我國教師專業標準落實情形，由高至低分別為專業實踐、專業知能、專業投入。 三、《中華民國教師專業標準指引》尚有滾動式修正的必要，未來可修正並持續實踐，以落實標準本位師資培育的政策。 四、建議未來教師專業標準修正可增加內涵有 : 具備素養導向教學能力；校訂課程發展與實踐能力；配合師資培育白皮書實施「教學軌」，以利教師展現協作與領導能力；以及增訂教師針對第二專長授課領域進行專業成長等標準。 Since 1990 standard-based teacher education has become the world's teacher education development trend. In 2016, the Ministry of Education of Taiwan announced the Guidelines for Teacher Professional Standards of the Republic of China to establish standard-based teacher education. Teacher professional standards have the functions of enhancing the quality of pre-service teacher education and the professional development for in-service teachers. The purposes of this study are to analyze the appropriateness and implementation of Taiwan's teacher professional standards and explore the future revision direction of these standards. This study also examined the professional standards of teachers in the United States, the U.K., and Taiwan through a literature review and conducted two rounds of a Delphi technique questionnaire survey to gather the consensus of 12 experts, who include scholars, supervisors of educational administrations, and primary school principals. The conclusions of this study are summarized as follows. 1. Ten teacher professional standards in Taiwan have high appropriateness. 2. The ranking of the implementation status of teachers' professional standards in Taiwan is professional practice, professional knowledge, and professional input. 3. Taiwan's Guidelines for Teacher Professional Standards need to be revised regularly. In the future, schools can also revise and continue to practice and implement the policy of standard-based teacher education. 4. It is recommended that a revision of the professional standards in the future can add the following: Possess competence-oriented teaching ability, enhance the curriculum development and practical abilities of the school, establish a teaching track proposed in Teacher Education White Paper, demonstrate collaboration and leadership skills, and update the teachers' professional growth regulations for second expertise.